Back-to-back MOS–Schottky (Pt–SiO2–Si–C–Pt) nano-heterojunction device as an efficient self-powered photodetector: one step fabrication by pulsed laser deposition - Shaikh, P. A.; Thakare, V. P.; Late, D. J.; Ogale, S. (Nanoscale, 2014)
An efficient self-powered photodetector design involving a C–Si hetero-interface with back-to-back MOS–Schottky (Pt–SiO2–Si–C–Pt) device action is presented. Pulsed laser deposition of a carbon thin film is used which dynamically removes the native surface oxide to form the desired Schottky interface. The combined device action yields two orders of magnitude photoresponse at zero bias.